2021
DOI: 10.1111/jcmm.16621
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells ameliorate silica‐induced pulmonary fibrosis by inhibition of inflammation and epithelial‐mesenchymal transition

Abstract: Silicosis is a devastating occupational disease caused by long‐term inhalation of silica particles, inducing irreversible lung damage and affecting lung function, without effective treatment. Mesenchymal stem cells (MSCs) are a heterogeneous subset of adult stem cells that exhibit excellent self‐renewal capacity, multi‐lineage differentiation potential and immunomodulatory properties. The aim of this study was to explore the effect of bone marrow‐derived mesenchymal stem cells (BMSCs) in a silica‐induced rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Lung cell EMT plays an important role in ventilationassociated lung fibrosis, which contributes to the poor outcomes of patients with ARDS. Numerous studies have indicated that inhibition of the EMT process can ameliorate pulmonary fibrosis [24]. Those studies have also shown that inositol suppresses cell motility and invasiveness by inducing cytoskeletal modifications that induce an EMT reversion in breast cancer cells [25], suggesting that inositol can inhibit the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cell EMT plays an important role in ventilationassociated lung fibrosis, which contributes to the poor outcomes of patients with ARDS. Numerous studies have indicated that inhibition of the EMT process can ameliorate pulmonary fibrosis [24]. Those studies have also shown that inositol suppresses cell motility and invasiveness by inducing cytoskeletal modifications that induce an EMT reversion in breast cancer cells [25], suggesting that inositol can inhibit the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, these enzymes regulate the levels of angiotensin, converting it into inactive metabolites. Combining viruses with receptors blocks the enzymatic activity of the latter, which results in an increase in the concentration of the hormone inside the cells and ultimately their death [20].…”
Section: Covid-19 Pathogenesismentioning
confidence: 99%
“…Absorption of damaged cells results in the release of small alarmins, also known as damage-associated molecular patterns (DAMPs). These molecules are recognized by toll-like receptors located on the surface of dendritic cells and leukocytes [20]. Binding of DAMPs activates in these cells the MyD88 adapter protein-dependent signalling pathway through which the nuclear factor kappa-light-chain-ehancer of activated B cells (NFκB) is activated.…”
Section: Covid-19 Pathogenesismentioning
confidence: 99%
“…4 However, the clinical symptoms of the disease develop rapidly, mainly inflammation and systemic features, pathologically dominated by excessive epithelial-mesenchymal transformation (EMT) and extracellular matrix (ECM) effects. 5 This can lead to increased mortality among younger workers. Furthermore, the prognosis of acute silicosis is poor, with patients often progressing to chronic respiratory failure, cor pulmonale, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Silicosis is caused by long‐term inhalation of significant quantities of free silica dust, an occupational disease primarily characterized by pulmonary fibrosis, which is considered primarily to be a disease with a long incubation period (>20 years) 4 . However, the clinical symptoms of the disease develop rapidly, mainly inflammation and systemic features, pathologically dominated by excessive epithelial‐mesenchymal transformation (EMT) and extracellular matrix (ECM) effects 5 . This can lead to increased mortality among younger workers.…”
Section: Introductionmentioning
confidence: 99%